(untitled) (Literary Voice, 2023)
Human beings are inherently storytelling creatures. Whatever they do, think, speculate, speak, or even dream does follow a narrative – a pattern that essentially tells a story. Coherence in storytelling is probably a naturalized phenomenon, necessarily inbuilt. Interestingly, the ability of narration and gaining wisdom both are something which happen throughout one’s lifetime. It has been observed time and again that gerontologists have shown intertwining dimensions of ageing and these therefore, in turn, attach increasing importance to the study of gerontology –they include ‘temporal’, ‘spiritual’ and ‘poetical’ aspects of growing. Arriving at the human tendency of storytelling, it can be stated that the narrative of any story is something that human beings use to understand the ‘temporality’ of life, one with which they attribute meaning and logic and hence add coherence to their life, overtly or otherwise. Thus, the purpose of this essay obviously would be to question the ‘claims’ of this ‘age’ and ‘ageing’ narrative of many gerontologists which in turn can be substantiated by fictional characters like Hagar Shipley from Margaret Laurence’s The Stone Angel and also Nariman Vakeel from Rohinton Mistry’s Family Matters and also question how certain age-old attributes of ageing can be questioned through these literary texts